Secondary bending moment of trapezoid web beam under shear loading - Fong, Shiau Ween (2006)
In structural and fabrication technology, new techniques of optimized steel structures design have been developed. One of the developments in steel structure design is the introduction of trapezoidal web beam. One of the phenomena being studied for the trapezoid web beam is the secondary bending moment which is induced in the flanges of section subjected to shear loading in the web, due to the corrugation of the web. A parametric study was carried out to develop a formula for the secondary bending moment. The parametric study involved in this study are depth of web, D, width of flange, B, thickness of flange, T and thickness of web, t. This study was carried out by using finite element method. The formula of secondary bending moment has been successfully derived and can be used for any other sections of trapezoid web beam with same corrugation thickness and corrugation angle.